2022
DOI: 10.1039/d2cy01406h
|View full text |Cite
|
Sign up to set email alerts
|

Advanced photocatalytic performance of PVP-modified BiOBr materials for the removal of 2,4-DCP and mechanism insight

Abstract: The BiOBr material is induced by PVP at room temperature to form an efficient visible light catalyst for removing non-dye organic pollutants from wastewater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The combination of photocatalysts with PVP results in the formation of nanocomposite materials, leading to a significant enhancement in photocatalytic performance. For instance, the BiOBr-PVP flower-like microsphere structure composite has demonstrated efficient degradation of 2,4-dichlorophenol [39], ofloxacin (OFL)/norfloxacin (NOR) [40], Cr (VI) [41], Rhodamine B (RhB), and diclofenac [42]. Zhiguo Zhang et al [43] demonstrated that the ultra-fine PVP-BiO 2−x nanomaterial, with a particle size distribution ranging from 5 to 10 nm, exhibited enhanced absorption capacity in the visible light spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of photocatalysts with PVP results in the formation of nanocomposite materials, leading to a significant enhancement in photocatalytic performance. For instance, the BiOBr-PVP flower-like microsphere structure composite has demonstrated efficient degradation of 2,4-dichlorophenol [39], ofloxacin (OFL)/norfloxacin (NOR) [40], Cr (VI) [41], Rhodamine B (RhB), and diclofenac [42]. Zhiguo Zhang et al [43] demonstrated that the ultra-fine PVP-BiO 2−x nanomaterial, with a particle size distribution ranging from 5 to 10 nm, exhibited enhanced absorption capacity in the visible light spectrum.…”
Section: Introductionmentioning
confidence: 99%